Laparoscopic splenectomy for a large multilocular splenic cyst with elevated CA19-9: Report of a case - Yoh, Tomoaki (Elsevier, 2013)
INTRODUCTION: Because splenic cysts are rare, a definitive treatment regime for these cysts remains unclear. We report a case of a large multilocular splenic cyst with elevated carbohydrate antigen 19-9 (CA19-9) levels, which was successfully treated with laparoscopic splenectomy. PRESENTATION OF CASE: A 22-year-old female was admitted to our hospital with severe left upper abdominal pain. Serum CA19-9 level was mildly elevated (65 U/ml). Computed tomography revealed a 25-cm long spleen with multilocular cystic lesions, for which an emergency laparoscopic splenectomy was performed. Histological findings revealed that the lesion was a benign true cyst, and immunostaining analyses showed that the epithelium was CA19-9-positive. DISCUSSION: Although some spleen-preserving approaches have been reportedly used, splenic cyst recurrence usually occurs in true cyst cases, wherein the cyst is incompletely removed. Most reported cases of splenic cysts producing CA19-9 are true cysts. CONCLUSION: The treatment approach should be decided on the basis of the type, shape, location, and even CA19-9 levels of the splenic cyst.